“Saving the crippled foot” – a study on diabetic foot ulcers and its salvage using flap surgeries - Akhil Xavier Joseph; Latheesh Leo; Mohieb Mustak Ahamed; Tanya Mohanraj; Vivian D'Almeida (Journal of the Foot & Ankle)
Objective: Emphasize the importance of a comprehensive and aggressive management with surgical debridement and flap-based reconstruction of defects in patients with diabetic foot ulcers (Ganga Class 3), and in turn, focusing on limb salvage. Methods: A retrospective cohort analysis was conducted on 40 patients with Ganga Class 3 diabetic foot submitted to flap surgeries between 2019 and 2022. These surgeries included both free and local flaps, and patients were followed postoperatively to monitor complications such as flap necrosis, infection, and the need for amputation. A pedobarogram was performed after wound healing to assess the risk of ulcer recurrence. Results: The mean age of the study population was 58.5 years, with 75% being male. Most ulcers (60%) were located in the hindfoot, with large hindfoot ulcers often requiring anterolateral thigh-free flaps, which showed excellent long-term outcomes. While effective for smaller defects, local flaps demonstrated higher complication rates, particularly flap necrosis in reverse sural artery flaps. Despite these complications, flap surgeries were largely successful, with only one patient requiring amputation, achieving significant success in limb salvage. Conclusion: Given that India is considered the diabetic capital of the world, with 85% of amputations preceded by foot ulcers, this study highlights the potential for surgical management of diabetic foot ulcers, regardless of size or location,n emphasizing the importance of limb salvage in improving patient outcomes. Level of evidence IV.